Estudio para la Declaratoria de Patrimonio Intangible a la Fiesta del Pawkar Raymi del Cantón Colta Provincia de Chimborazo. - Torres Jara, Gabriela Natalia (2012)
This research called "STUDY FOR A DECLARATION OF INTAGIBLE ASSETS OF THE PAWKAR RAYMI FEAST IN COLTA CANTON –CHIMBORAZO-ECUADOR" aims to revitalize, strengthen historical memory and enhancement of our cultural identity as Andean peoples. Andean communities have different manifestations as the flourishing agricultural cycle with its presence of flowers, medicinal plants, and sacred food, so grains and fruit as a gift of nature that is the PachakamakYaya (God, Jehovah, and Allah) allows to the human community the occasion for the celebration and thanks to the mutual love of Pachamama (Nature) and YayaPachakamak (God). The PawkarRaymi is an ancient festival focused on sharing food and drink during the celebration, expressing the feeling and living through rituals of thanks to Mother Earth, the celebration is accompanied by figures representing the activities of the community such as the Yaya Mama Carnival Shalva and demonstrating the duality of Andean worldview, accompanied by the music, folklore and local food. The proposal and scope of the research aim to record and make the proper, theoretical and legal framework to declare this event as an Intangible Cultural Heritage. Local government and authorities together with the Institute of Cultural Heritage and UNESCO promote conservation PCI politically, socially appropriate and in synergy with the social and economic development of the zone and province.